Data From Early Childhood Educators’ Work and Stress Study - Randi A. Bates; Jaclyn M. Dynia; Bailey E. Martin (Journal of Open Psychology Data)
This paper describes a longitudinal dataset of perceived job stress, perceived general stress, financial stress, demographics, and educational center characteristics of center-based early childhood educators in the Midwest across the academic year 2021–2022. At four time points, a convenience sample of 67 educators completed electronic surveys. At the first two time points, a subset provided hair cortisol samples to estimate physiological chronic stress. The publicly available, de-identified data can provide nuanced research and teaching opportunities into educators’ stressors during a dynamic period of the COVID-19 pandemic.